Study on Effect of HCl and CaCl2 on Extraction of Heavy Metals From Contaminated Soils - Ahmad, Anwar (Asian Journal of Chemistry, 2010)
The efficiencies of hydrochloric acid and calcium chloride were tested for extracting metals from contaminated soils. The selectivity of the acids and CaCl2 toward soil adsorption sites, the lower the pH in the extracts and the more soil metals Pb, Cd and Zn, Ni could be extracted. The concentration of heavy metals observed was in Yamuna river were, Cd 0.18, Zn 1.3, Ni 1.6, Pb 1.38 mg/L and in submerged plants were, Cd 0.3, Zn 1.19, Ni 0.8, Pb 0.97 mg kg-1 in Okhla and in Yamuna river Cd 0.09, Zn 0.98, Ni 1.02 and Pb 0.95 mg/L and in submerged plants Cd 0.0 9, Zn 0.9, Ni 1.9 and Pb 0.3 mg kg-1, respectively in Wazirabad. This indicates that industry effluents could be one of the cause pollution and point sources of metals pollution in the Yamuna river. The Okhla point have low pH compare to Wazirabad (pH 6.2-7.2 and 7.2-9.0) and Okhla soil releases more heavy metals like Cd, Pb, Zn and Ni in site Okhla > Wazirabad. The correlation analysis revealed that Cd and Pb fraction of metals in soil with pH and salt was highly correlated (p < 0.001), whereas the Zn and Ni fraction was not better correlated (p < 0.001).